Esophagojejunal anastomotic leak managed with self expandable metallic stent - Annapillai, Arvind Madurandagam; Ramachandran, Biggs Saravanan; Ponniah, Senthilkumar; V., Hemamala; B., Kesavan; Karunakaran, Premkumar; Raju, Prabhakaran; G., Manoharan; Murugesan, Chandramohan Servarayan; Muhammed, Mohammed Ali (Journal of Digestive Endoscopy, 2013)
Esophagealjejunal anastomotic leak after gastrectomy is a serious surgical emergency with high mortality. This report describes a 57-year-old male with esophagojejunal anastomotic leak following total gastrectomy for gastric cancer and was managed successfully with self-expandable metallic stent. To our knowledge this is the first such report from India. This case report highlights the need of interdisciplinary coordination in managing this difficult clinical situation. Endotherapy with self-expandable metallic stent (SEM) provided twin benefits of improving respiratory embarrassment and the joy of eating. Therapy of such difficult cases must be individualized; however, and SEM stent usage is a viable option (J Dig Endcsc 2013;4(1):13–15)
Keywords: Anastomotic leak; SEM stent; Endotherapy; Esophagojejunal leak